2022
DOI: 10.1111/jhn.12990
|View full text |Cite
|
Sign up to set email alerts
|

Biology of human milk oligosaccharides: From basic science to clinical evidence

Abstract: Human milk oligosaccharides (HMOs) have been researched by scientists for over 100 years, driven by the substantial evidence for the nutritional and health benefits of mother's milk. Yet research has truly bloomed during the last decade, thanks to progress in biotechnology, which has allowed the production of large amounts of bona fide HMOs. The availability of HMOs has been particularly crucial for the renewed interest in HMO research because of the low abundance or even absence of HMOs in farmed animal milk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 196 publications
(487 reference statements)
0
40
0
1
Order By: Relevance
“…Human milk is rich in a plethora of structurally diverse oligosaccharides, collectively known as human milk oligosaccharides (HMOs). They form the third largest solid component of human milk and come in a large structural variety based on the combination of their monosaccharide subunits: fucose, N -acetyl-neuraminic acid, N -acetyl-glucosamine, galactose, and glucose ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human milk is rich in a plethora of structurally diverse oligosaccharides, collectively known as human milk oligosaccharides (HMOs). They form the third largest solid component of human milk and come in a large structural variety based on the combination of their monosaccharide subunits: fucose, N -acetyl-neuraminic acid, N -acetyl-glucosamine, galactose, and glucose ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…These diets contained one of three individual human milk oligosaccharides (HMOs; 2′-fucosyllactose (2′-FL), 6′-siaylyllactose (6′-SL), lacto-N-neo-Tetraose (LNnT)), a digestion resistant maltodextrin, or a complex mixture of MACs found within gum arabic. These MACs were selected based on evidence that HMOs impact SCFA production by gut microbes [37] and have a variety of beneficial effects on the eukaryotic host [38] and to understand whether the SCFAs produced by other structurally unrelated plant polysaccharides (distinct from fructans or the complex mixture of MACs present in standard rodent diets) impact C. difficile infection. We observed that these MAC types differentially impact C. difficile burdens and that out of these additional MACs tested, maltodextrin was the only one that consistently reduced C. difficile burdens below detection ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…377 HMOs are another clinically relevant glycan class with extensive nutritional and health benefits for infants. 378,379 Because of their extreme complexity and diversity their comprehensive analysis, especially in HT mode, remains challenging. Significant progress in the quantification of this diverse glycan class has been made in the past decade 16,17,380,381 (Figure 15), facilitating analysis in large-scale studies.…”
Section: Ht-glycomics In Clinical Studiesmentioning
confidence: 99%
“…Significant progress in the quantification of this diverse glycan class has been made in the past decade ,,, (Figure ), facilitating analysis in large-scale studies. Current knowledge on associations of HMO content with infant growth and health status is extensively reviewed by Sprenger et al Most notably, a study done by HPLC-FLD analysis of 2-AB labeled oligosaccharides from 410 human milk samples showed that HMO concentrations and profiles differ between healthy women from different geographical regions . Analysis of HMOs by nano-LC-chip TOF-MS in two cohorts of 303 Malawian mother–infant sets showed a lower abundance of fucosylated and sialylated HMOs in breast milk of nonsecretor mothers (negative for the functional enzyme encoded by the fucosyltransferase 2 gene), whose infants were minimal compared to those showing normal growth .…”
Section: Applicationsmentioning
confidence: 99%